A new species of the Hydaticus sexguttatus species group from India (Coleoptera: Dytiscidae) - Wewalka, Günther; Hájek, Jiří (Zootaxa, 2025)
Hydaticus kadumane sp. nov., belonging to the Hydaticus (Prodaticus) sexguttatus species group, is described from the Indian state Karnataka. In habitus and dorsal colouration, it is similar to several species from Borneo Island and the Philippines, but it can be undoubtedly recognised based on the shape of male genitalia. Photographs of the dorsal habitus and male median lobe of the aedeagus are provided.